Landscapes of Lake Baikal: «To protect or to build» Town planning motivations of the stable development of the region - Bolshakov, Andrei (project baikal, 2006)
Building, planning, engineering facilities of the inhabited places of Lake Baikal and organization of the recreational areas for tourists, as well as organization of the particularly reserved natural territories should maintain everlastingly untouched the beauty and the cleanness, the natural diversity and the uniqueness of the nature of Lake Baikal, that makes it glorious and attracts tourists and inhabitants so much. Is it possible? And how to combine technical conditions of civilization, to which we have got used so much (energy supply, canalization, asphalt roads, automobile transport, oilpipelines, developed cities and villages), and aspiration of many investors, who would like to organize a profitable tourist business, together with the goal to protect the nature of Lake Baikal. To protect or to develop the landscapes of Lake Baikal, and which landscapes to urbanize and which to restore, and how to equip the developed territories, and how to maintain the protected natural landscapes–these questions compose a complex national task. Its accomplishment is firstly based on studying and maintaining the diversity of landscapes of the region and its importance as the global natural heritage. Secondly, the stable development of the region is possible only when solving the conflicts of landutilization motivations in a right way at the expense of building the rational network of the Baikal landscapes from the reserved to the urbanized ones.